2021
DOI: 10.1007/s42764-021-00049-8
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Claspin in regulation of DNA replication, replication stress responses and oncogenesis in human cells

Abstract: Human cells need to cope with the stalling of DNA replication to complete replication of the entire genome to minimize genome instability. They respond to “replication stress” by activating the conserved ATR-Claspin-Chk1 replication checkpoint pathway. The stalled replication fork is detected and stabilized by the checkpoint proteins to prevent disintegration of the replication fork, to remove the lesion or problems that are causing fork block, and to facilitate the continuation of fork progression. Claspin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 134 publications
(181 reference statements)
0
11
0
Order By: Relevance
“…Claspin is a multifunctional crucial protein that are essential for the maintenance of genome stability (5) . Claspin has been constituted as a promising therapeutic target in neoplasms, specifically for chemo and radio-sensitization (20) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Claspin is a multifunctional crucial protein that are essential for the maintenance of genome stability (5) . Claspin has been constituted as a promising therapeutic target in neoplasms, specifically for chemo and radio-sensitization (20) .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to its function in DNA replication, Claspin contains DNA repair pathways like repair of nucleotide excision (21) , homologous recombination and mismatch repair (22) . Therefore, this dual effect of Claspin in carcinogenesis require further investigation (5) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported novel functions and mechanisms of Claspin actions in replication initiation and in replication checkpoint activation [3-4, 45-46]. More recently, we reported that Claspin regulates growth restart from serum starvation by activating the PI3K-PDK1-mTOR pathway [45].…”
Section: Introductionmentioning
confidence: 99%
“…Claspin is involved in the ATR-Chk1 signaling axis in the replication stress response as an essential mediator [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%